Aqueous dispersions of nanostructures formed through the self-assembly of iminolipids with exchangeable hydrophobic termini. Issue 26 (23rd June 2017) - Li, Wen; McManus, Daryl; Liu, Han; Casiraghi, Cinzia; Webb, Simon J.
Abstract : Cationic lipids that have an exchangeable imine terminus can self-assemble into vesicles and stabilize graphene dispersions in water. Abstract : The addition of amines to an aldehyde surfactant, which was designed to be analogous to didodecyldimethylammonium bromide, gave exchangeable "iminolipids" that self-assembled to give stable aqueous dispersions of nano-sized vesicles. For example, sonication of suspensions of the n -hexylamine-derived iminolipid gave vesicles 50 to 200 nm in diameter that could encapsulate a water-soluble dye. The iminolipids could undergo dynamic exchange with added amines, and the resulting equilibrium constants ( K rel ) were quantified by 1 H NMR spectroscopy. In the absence of lipid self-assembly, in CDCl3, the assayed primary amines gave very similar K rel values. However in D2 O the value of K rel generally increased with increasing amine hydrophobicity, consistent with partitioning into a self-assembled bilayer. Amines with aromatic groups showed significantly higher values of K rel in D2 O compared to similarly hydrophobic alkylamines, suggesting that π–π interactions favor lipid self-assembly. Given this synergistic relationship, π-rich pyrenyliminolipids were created and used to exfoliate graphite, leading to aqueous dispersions of graphene flakes that were stable over several months.